ANALYSIS OF TEACHER PROBLEMS IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN ELEMENTARY SCHOOL NEGERI 1 LAMBHEU, ACEH BESAR DISTRICT - Alviana, Rahma; Safiah, Intan; Fitri, Aida (Elementary Education Research, 2024)
The implementation of the independent curriculum will be implemented at SD Negeri 1 Lambheu starting in the 2022/2023 school year and will be implemented in stages. In implementing learning, there are problems in planning, implementing and evaluating learning. The problem in this research is "What are the problems of teachers in implementing the independent curriculum at SD Negeri 1 Lambheu, Aceh Besar Regency?". Therefore, this research aims to describe teacher problems in implementing the Independent Curriculum at SD Negeri 1 Lambheu, Aceh Besar Regency. The approach used in this research is a qualitative approach with descriptive research type. The data collection process was carried out using observation, interview and documentation techniques. Data analysis carried out by researchers used data reduction methods, data presentation and drawing conclusions. The results of the research show that the problems faced by teachers are in preparing learning tools such as CP, TP, ATP, and teaching modules, minimal use of learning models and methods, limited media, determining projects that suit the theme, insufficient time allocation in project implementation, and carry out assessments during project implementation. The results of these interviews and observations were analyzed and then presented in descriptive form.